Correlation of the National Institutes of Health Patient Reported Outcomes Measurement Information System Scales and Standard Pain and Functional Outcomes in Spine Augmentation - Shahgholi, L.; Yost, K.J.; Kallmes, D.F. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: The recently developed National Institutes of Health PROMIS initiative provides reliable and valid measures across many health domains. We correlated changes in pain-related PROMIS measures and changes in both an NRS and the RMDI in patients undergoing spine augmentation. MATERIALS AND METHODS: Fifty patients, composed of 26 women (40–91 years of age; mean, 72.6 years) and 24 men (42–78 years of age, mean, 67.5 years) were enrolled in the study. They were asked at initial presentation and at 30 days to rate the intensity of their pain in the past 24 hours by using a 0–10 pain NRS as well at the 23-item RMDI. Study subjects also completed 3 different PROMIS short forms, including physical function, pain behavior, and pain interference. The Spearman correlation was used to assess the correlation between the scales. The RCI × 1.96 was calculated for each measurement tool as an indicator of change. RESULTS: All instruments were responsive to detection of change during 1 month (all, P < .0001). Correlations between changes in physical function, pain interference, and pain behavior PROMIS scores and changes in RMDI scores were 0.37, 0.44, and 0.42, respectively. Direction of changes (declines versus improvements) in RMDI and other scales were the same in approximately 60% of patients. CONCLUSIONS: All measures evaluated had adequate and comparable psychometric properties. The choice of which measure to use depends on the clinical intent of the intervention. IRTitem response theoryMIDminimally important differencesNRSnumerical rating scalePROMISPatient Reported Outcomes Measurement Information SystemRCIReliable Changes IndexRMDIRoland-Morris Disability IndexSEMstandard error of measurement